Best American short stories 2024 : selected from U.S. and Canadian magazines - Groff, Lauren; Pitlor, Heidi (Best American series., 2024)
"This abundance led to a volume of robust stories with the nerve to push against narrative expectations. The Best American Short Stories 2024 boasts a collection of twenty stories that "buzz with their own strange logic." A man becomes a tourist in his own hometown. An unemployed jeweler sails in an antique slave ship. A therapist decides to call an ex-patient years after their last session"--